Beta-blockers in patients with liver cirrhosis: Pragmatism or perfection? - Sauerbruch, Tilman; Hennenberg, Martin; Trebicka, Jonel; Schierwagen, Robert (Frontiers in Medicine, 2023)
With increasing decompensation, hyperdynamic circulatory disturbance occurs in liver cirrhosis despite activation of vasoconstrictors. Here, the concept of a therapy with non-selective beta-blockers was established decades ago. They lower elevated portal pressure, protect against variceal hemorrhage, and may also have pleiotropic immunomodulatory effects. Recently, the beneficial effect of carvedilol, which blocks alpha and beta receptors, has been highlighted. Carvedilol leads to "biased-signaling" via recruitment of beta-arrestin. This effect and its consequences have not been sufficiently investigated in patients with liver cirrhosis. Also, a number of questions remain open regarding the expression of beta-receptors and its intracellular signaling and the respective consequences in the intra- and extrahepatic tissue compartments. Despite the undisputed role of non-selective beta-blockers in the treatment of liver cirrhosis, we still can improve the knowledge as to when and how beta-blockers should be used in which patients.